2015
DOI: 10.1016/j.chom.2015.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Malaria Sporozoites Traverse Host Cells within Transient Vacuoles

Abstract: Plasmodium sporozoites are deposited in the host skin by Anopheles mosquitoes. The parasites migrate from the dermis to the liver, where they invade hepatocytes through a moving junction (MJ) to form a replicative parasitophorous vacuole (PV). Malaria sporozoites need to traverse cells during progression through host tissues, a process requiring parasite perforin-like protein 1 (PLP1). We find that sporozoites traverse cells inside transient vacuoles that precede PV formation. Sporozoites initially invade cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
169
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(172 citation statements)
references
References 40 publications
3
169
0
Order By: Relevance
“…They further validated this finding through microscopy studies showing LC3 deposition on the parasitophorous vacuole, and colocalization of parasites with Lysotracker red (LTR) stained acidic vesicles in response to IFN-γ stimulation. Notably, these results are in line with a study of the rodent parasite P. yoelii, which demonstrated that LTR-positive vesicles colocalized with sporozoites that failed to egress from their traversal vacuoles within hepatocytes (9).…”
supporting
confidence: 78%
“…They further validated this finding through microscopy studies showing LC3 deposition on the parasitophorous vacuole, and colocalization of parasites with Lysotracker red (LTR) stained acidic vesicles in response to IFN-γ stimulation. Notably, these results are in line with a study of the rodent parasite P. yoelii, which demonstrated that LTR-positive vesicles colocalized with sporozoites that failed to egress from their traversal vacuoles within hepatocytes (9).…”
supporting
confidence: 78%
“…Because we have codeveloped a humanized mouse model for P. vivax hypnozoite persistence (4), this question can now be further explored and will be a subject of our future study. Moreover, a recent study in P. yoelii by Risco-Castillo and colleagues (42) showed that parasites that fail to egress from their transient traversal vacuoles are colocalized with host lysosomes. Whether the LAP-like noncanonical autophagy process described here with P. vivax is involved in this process is of interest and may be a subject of further study.…”
Section: Liver-stage P Vivax Colocalizes With Lc3 and Ltrmentioning
confidence: 99%
“…All Apicomplexa have in common the sporozoite stage. Unlike blood stages, the sporozoite is an accessible extracellular stage, which is characterized by its motility and its ability to traverse cells (26)(27)(28) without forming a parasitophorous vacuole. Thus, this parasite stage has an opportunity to directly interact with host tRNAs.…”
Section: Significancementioning
confidence: 99%